PEMIKIRAN ISLAM KONTEMPORER DALAM BENTURAN BUDAYA - M. Hasbi Amiruddin (Universitas Islam Negeri Ar-Raniry, 2014)
This article presents how contemporary Islamic thought which has been tr ying to find a breakthrough in order to improve the quality of life of the Muslims, then collide with a culture that has been attached to the public, the results of a long legacy of their predecessors. This phenomenon which occurred in Indonesia, because the Indonesian archipelago was not found to be the legacy of Islamic thought advances era (570-1250) in various fields of religion, science and technology. In Indonesia, even contemporary Islamic thought that tr ying to get back to the essence of Islam, which is the religion that is always authentic from times to times and in all palces, always in conflict with the culture of the people who have been acute determinism school of thought.